Coincident correlations of growth and cash flow in banking - Dahl, Drew (Journal of Banking & Finance, 2012)
Prior empirical research indicates that loan growth in the banking industry is positively related to cash flow. I offer an alternative methodology that is better able to capture the effect of cash flow on loan growth while controlling for the potentially coincident effect of loan growth on cash flow. Using a sample of 171,389 observations on banks, 1986–2007, I find that causality runs more consistently from growth to cash flow than from cash flow to growth. This extends prior empirical research by Houston and James (1998) and Campello (2002) on cash flow sensitivities in the banking industry.